2015
DOI: 10.1016/s0187-6236(15)72159-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved rainfall estimation over the Indian monsoon region by synergistic use of Kalpana-1 and rain gauge data

Abstract: RESUMENEn este trabajo se busca calcular la precipitación en la región del monzón de la India mediante el uso sinérgico de datos pluviométricos y del algoritmo multiespectral de precipitación del Sistema Nacional de Satélites de la India (IMSRA, por sus siglas en inglés), obtenido mediante el satélite geostacionario -temporales del satélite Kalpana-1, así como de estimaciones pluviométricas precisas. Se realiza un análisis progresiva se aplica a una resolución de 1º × 1º determinada por el análisis de autocorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…7 Meteorological sub-divisional scale seasonal JJAS accumulated rainfall (mm) and its departure from the normal (given in parentheses) using a Kalpana-1 IMSRA, b GSMaP-NRT, c TMPA-3B42 and d IMD-SRG data sets for the southwest monsoon of 2013 IMSRA and TMPA data sets with respect to IMD-SRG based estimates clearly shows the potential of Kalpana-1 derived rainfall product for monsoon monitoring at meteorological sub-divisional scale. Furthermore, it is recently shown that the combined use of IMSRA and rain gauge observations provides better rainfall estimates over the Indian monsoon region (Gairola et al 2015). Thus, the merged satellite-gauge rainfall product would provide better rainfall estimates at meteorological sub-divisional scale.…”
Section: Assessment Of Ismr At Seasonal Time Scalementioning
confidence: 99%
“…7 Meteorological sub-divisional scale seasonal JJAS accumulated rainfall (mm) and its departure from the normal (given in parentheses) using a Kalpana-1 IMSRA, b GSMaP-NRT, c TMPA-3B42 and d IMD-SRG data sets for the southwest monsoon of 2013 IMSRA and TMPA data sets with respect to IMD-SRG based estimates clearly shows the potential of Kalpana-1 derived rainfall product for monsoon monitoring at meteorological sub-divisional scale. Furthermore, it is recently shown that the combined use of IMSRA and rain gauge observations provides better rainfall estimates over the Indian monsoon region (Gairola et al 2015). Thus, the merged satellite-gauge rainfall product would provide better rainfall estimates at meteorological sub-divisional scale.…”
Section: Assessment Of Ismr At Seasonal Time Scalementioning
confidence: 99%
“…The sparse distribution of rain gauges and weather radars mainly in mountainous and deeper oceanic regions limits various applications on global and regional scale. On the other hand, space-borne sensors provide homogeneous spatial and temporal distribution of rainfall (Gairola et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To merge rain gauge observations with INSAT (Indian National SATellite) satellite retrieved rainfall at 1° × 1° spatial resolution, Roy Bhowmik and Das (2007) used an objective analysis method over the Indian landmass for ISM rainfall. Gairola et al (2015) developed a merged rainfall method by blending rain gauge observations with geostationary Kalpana-1 satellitederived IMSRA (INSAT retrieved Multi-Spectral Rainfall Algorithm) rainfall estimates using an objective criterion of successive correction method. Authors found considerable improvements in terms of correlation, bias and root-mean-square error after objective analysis, especially over the regions where density of rain gauge was better.…”
Section: Introductionmentioning
confidence: 99%
“…However, a suitable bias correction in IMSRA rainfall data is needed before its use for drought monitoring and hydrological applications. Recently, Gairola, Prakash, and Pal (2015) demonstrated that the synergistic use of IMSRA and rain-gauge observations would provide better rainfall estimates over the Indian monsoon region as it benefits from the relative merits of both data sources. Hence, combined Kalpana-1 and rain-gauge rainfall estimates would be better for meteorological drought monitoring over India.…”
mentioning
confidence: 99%